2019
DOI: 10.1002/nafm.10309
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Juvenile Chinook Salmon Rearing Habitat Potential Prior to Species Reintroduction

Abstract: Successful Pacific salmon reintroduction into rivers where they have been extirpated requires understanding the range of habitats and environmental conditions that currently exist and their ability to support target species. Chinook Salmon Oncorhynchus tshawytscha were extirpated from the San Joaquin River, California, over 60 years ago and are targeted for reintroduction into the system. To assess the remaining habitat along the longitudinal lower San Joaquin River gradient, juvenile Chinook Salmon were reare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 58 publications
1
10
0
Order By: Relevance
“…2020), although downstream rearing in floodplains, when available, may improve subsequent growth and survival (Zeug et al. 2019), and years of high flow also support greater survival (Zeug et al. 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2020), although downstream rearing in floodplains, when available, may improve subsequent growth and survival (Zeug et al. 2019), and years of high flow also support greater survival (Zeug et al. 2020).…”
Section: Discussionmentioning
confidence: 99%
“…2016; Zeug et al. 2019). However, the risk of predation is also high and contingent on flow patterns (Lindley et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Successful reintroduction and management of salmonids in the Central Valley necessitates an improved understanding of the habitat conditions driving population level success at every life stage (Zeug et al 2019). Previous work investigating smolt outmigration in the San Joaquin River has focused on spatiotemporal patterns in mortality (Buchanan et al 2013(Buchanan et al , 2018Singer et al in prep 1 ), which is an important step towards informing actionable management (Perry et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…As a preliminary step in their reintroduction, Zeug et al. (2019) evaluated the growth of juvenile Chinook Salmon in four locations in the lower San Joaquin River. Their findings suggested that growth and survival within habitat types was dynamic across seasons and likely driven by changing water quality and prey availability.…”
Section: Figurementioning
confidence: 99%